Valuation, Optimal Asset Allocation and Retirement Incentives of Pension Plans - Sundaresan, Suresh; Zapatero, Fernando (Review of Financial Studies, 1997)
We provide a framework in which we link the valuation and asset allocation policies of defined benefits plans with the lifetime marginal productivity schedule of the worker and the pension plan formula. In turn, we examine the retirement policies that are implied by the primitives of the model and the value of pension obligations. Our model provides an explicit valuation formula for a stylized defined benefits plan. The optimal asset allocation policies consist of the replicating portfolio independent of the pension liabilities. We show that the worker with retire when the ratio of pension benefits to current wages reaches a critical value which depends on the parameters of the pension plan and the discount rate. Using numerical techniques we analyze the feedback effect of retirement policies on the valuation of plans and on the asset allocation decisions.